Pengaruh Literasi Keuangan, Konformitas Teman Sebaya, dan Kecemasan Finansial terhadap Perilaku Keuangan Generasi Z - Akmelia Zahra; Suparno Suparno; Fitra Dila Lestari (Indo Publishing, 2026)
This study aims to analyze the influence of Financial Literacy, Peer Conformity, and Financial Anxiety on the Financial Behavior of Generation Z in the Jabodetabek area. A quantitative approach was employed using an explanatory research design. Data were collected through online questionnaires distributed to 218 respondents selected through purposive sampling. After data cleaning, 217 respondents were analyzed using multiple linear regression with the Weighted Least Squares (WLS) method to address heteroscedasticity issues. The results show that Financial Literacy has a positive and significant influence on Financial Behavior (t = 6.840; p = 0.000), indicating that higher financial literacy leads to better financial management practices. Conversely, Peer Conformity does not have a significant influence on Financial Behavior (t = -0.724; p = 0.470), suggesting that social pressure from peers does not substantially affect financial decision-making among Generation Z. Similarly, Financial Anxiety does not have a significant influence on Financial Behavior (t = 0.381; p = 0.703), meaning that financial worries do not directly translate into changes in financial behavior. The Adjusted R Square value of 0.201 indicates that the three variables collectively explain 20.1% of the variation in Financial Behavior, while the remaining 79.9% is influenced by other factors outside the model.